Housing policy in the Republic of Korea - Kyung-Hwan Kim; Miseon Park (Asian Development Bank Institute (ADBI), 2016)
This paper evaluates housing policy in the Republic of Korea over the past several decades, describes new challenges arising from the changing environment, and draws lessons for other countries. The most important goals of the housing policy have been to alleviate housing shortages and to stabilize housing prices. To achieve these goals, the government has been engaging the private sector while establishing public sector institutions and legal framework, providing developable land, and allocating housing units to intended target groups. Thanks to the sustained and massive provision of new housing since the 1980s, the country's absolute housing shortage has been resolved, and overall housing conditions have improved substantially. Since the turn of the new millennium, enhancing the housing welfare of low-income households and the underprivileged has been added to housing policy goals. The supply of public rental housing was increased, and a housing benefit was introduced to address the new policy goal, but more work needs to be done. Today, the Republic of Korea also faces new housing challenges regarding the country's demographic and socioeconomic changes.
Keywords: P25; R21; R28; R31; R38; R52; 330; Korean housing policy; housing-macroeconomy nexus; rental housing market structural change